Are tai chi and qigong effective in the treatment of TBI? A systematic review protocol - Laskosky, Nicole Alexandra; Huston, Patricia; Lam, Wai Ching; Anderson, Charlotte; Zheng, Ya; Zhong, Linda L. D. (Frontiers in Aging Neuroscience, 2023)
Abstract Background: Traumatic brain injury (TBI) adversely affects both young and old and is a growing public health issue. A number of recent trends in managing TBI, such as sub-threshold aerobic activity, tailored multi-modal treatment strategies and the possible role of low-grade inflammation in those with persistent symptoms, all suggest that the physical and cognitive exercise of tai chi/qigong could have benefit. Method: Designed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the following databases will be searched: Medline, CINAHL Cochrane Library, EMBASE, China National Knowledge Infrastructure Database, Wan fang database, Chinese Scientific Journal Database, and Chinese Biomedical Literature Database. All clinical trials on mild, moderate and/or severe TBI with Tai chi and/or Qigong as the treatment group and any comparison group, in any setting will be included. Four reviewers will independently select studies; two reviewers for the English and two for the Chinese databases. Cochrane-based risk of bias assessments will be conducted on all included studies. An analysis will then be conducted with the grading of recommendation, assessment, development, and evaluation (GRADE) instrument. Results: This review will summarize the clinical trial evidence on tai chi/qigong for TBI including type of TBI, age/sex of participants, type and length of intervention and comparator, outcome measures, and any adverse events. The risk of bias will be considered, and the strengths and weaknesses of each trial will be analyzed. Discussion: The results of this review will be considered with respect to whether there is enough evidence of benefit to merit a more definitive randomized controlled trial and discover the neurological mechanism. PROSPERO registration number: CRD42022364385